2009
DOI: 10.1074/jbc.m109.047910
|View full text |Cite
|
Sign up to set email alerts
|

GCN2 Protein Kinase Is Required to Activate Amino Acid Deprivation Responses in Mice Treated with the Anti-cancer Agent l-Asparaginase

Abstract: Asparaginase depletes circulating asparagine and glutamine, activating amino acid deprivation responses (AADR) such as phosphorylation of eukaryotic initiation factor 2 (p-eIF2) leading to increased mRNA levels of asparagine synthetase and CCAAT/enhancer-binding protein ␤ homologous protein (CHOP) and decreased mammalian target of rapamycin complex 1 (mTORC1) signaling. The objectives of this study were to assess the role of the eIF2 kinases and protein kinase R-like endoplasmic reticulum resident kinase (PERK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 38 publications
11
93
0
Order By: Relevance
“…Immunoblot Analysis-Tissues were processed for SDS-PAGE and immunoblotting as described previously (6,16). Primary antibody for eIF2␣ phosphorylated at serine 51 was purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot Analysis-Tissues were processed for SDS-PAGE and immunoblotting as described previously (6,16). Primary antibody for eIF2␣ phosphorylated at serine 51 was purchased from Cell Signaling Technology (Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Suppression of the ISR by glutamine input has been shown to be critical for survival of several cancer cell and tumor types including neuroblastoma and breast cancer 65,97,98 . It was also observed that GCN2 is activated in mice in response to treatment with asparaginase 99 , which is approved by the US Food and Drug Administration (FDA) for the treatment of acute lymphoblastic leukemia (ALL) and may deplete serum asparagine and glutamine [100][101][102] .…”
Section: Protein Synthesis Trafficking and Stress Pathway Suppressionmentioning
confidence: 99%
“…GCN2, a serine-threonine kinase with a regulatory domain that is structurally similar to histidine-tRNA synthetase, is allosterically activated by uncharged tRNAs with amino acid deprivation (including glutamine deprivation) and in turn activates the integrated stress response (ISR) 96,214,215 . Glutamine can suppress GCN2 activation through its contribution to amino acid pools by aminotransferases 65,[97][98][99] . To control endoplasmic reticulum (ER) homeostasis, glutamine supports protein folding and trafficking through its contribution to uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) as part of the hexosamine biosynthesis pathway.…”
Section: Key Pointsmentioning
confidence: 99%
“…1B). To establish whether or not the JMJD3 gene is responsive to AA deprivation in vivo, mice were treated with the drug asparaginase, which depletes circulating asparagine and glutamine levels and activates the AAR (33). Analysis of mouse liver tissue showed that asparaginase treatment resulted in about a 2-fold increase in Jmjd3 mRNA (Fig.…”
Section: Aar-induced Mrna Expression For Jmjd3 In Cells Andmentioning
confidence: 99%